2013
DOI: 10.1002/jgrc.20139
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of bio‐optical inversion algorithms for remote sensing of Lake Superior's optical properties

Abstract: [1] Satellite remote sensing offers one of the best spatial and temporal observational approaches. However, well-validated satellite imagery has remained elusive for Lake Superior. Lake Superior's optical properties are highly influenced by colored dissolved organic matter (CDOM), which has hindered the retrieval of chlorophyll concentration through band-ratio algorithms. This study evaluated seven existing inversion algorithms. The top-performing inversion algorithm was tuned to a Lake Superior optical data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 56 publications
1
24
1
Order By: Relevance
“…At high levels of biomass in the MB, absorption is almost entirely due to phytoplankton. Our determination of the relative absorption budget for Lake Erie differs significantly compared to similarly depicted data from Lake Superior (Mouw et al, 2013a) and the global oceans (Figure 4 inset). Lake Superior is a system dominated by CDOM absorption with minimal phytoplankton and non-algal particle absorption, and occupies a region in the ternary plot that has no overlap with the Erie data.…”
Section: Absorptioncontrasting
confidence: 56%
See 1 more Smart Citation
“…At high levels of biomass in the MB, absorption is almost entirely due to phytoplankton. Our determination of the relative absorption budget for Lake Erie differs significantly compared to similarly depicted data from Lake Superior (Mouw et al, 2013a) and the global oceans (Figure 4 inset). Lake Superior is a system dominated by CDOM absorption with minimal phytoplankton and non-algal particle absorption, and occupies a region in the ternary plot that has no overlap with the Erie data.…”
Section: Absorptioncontrasting
confidence: 56%
“…Knowing the relative contribution to absorption provides insight into the retrieval accuracy of individual components from bio-optical algorithms. Mouw et al (2013a) showed that the accuracy of total absorption was good from algorithm inversions for Lake Superior, while the CDOM absorption component fared better than the phytoplankton absorption component. Given Lake Superior is a CDOM-dominated system with a very small contribution from phytoplankton to the overall absorption budget, the retrieval of chlorophyll concentration via inversion algorithms was not possible due to errors in derived CDOM absorption being greater than phytoplankton absorption values.…”
Section: Absorptionmentioning
confidence: 99%
“…In this study, images were processed with default settings in SeaDAS. Mouw et al (2013) found that the standard atmospheric correction worked best over Lake Superior. However, this evaluation was based on the blue-green region.…”
Section: Discussionmentioning
confidence: 99%
“…Ice cover is prevalent in winter and thus wintertime data are essentially non-existent. Satellite algorithms for biogeochemistry have only recently been developed (Mouw et al, 2013). The overall lack of understanding of the carbon cycle and related biogeochemical processes is of particular concern in light of the desire to better manage the lakes so that they can continue to sustainably support ecosystems and economies in the face of the many anthropogenic stressors (Great Lakes Restoration Initiative 2010, http://greatlakesrestoration.us/pdfs/glri_actionplan.pdf), including ocean acidification (NOAA, 2010, Phillips et al, 2015.…”
Section: Regional Settingmentioning
confidence: 99%
“…In addition, algorithms may not perform well in optically complex coastal waters and where the bottom contributes to the measured above-water reflectance. To some extent, these limitations can be addressed through the use of regionally tuned algorithms and use of multiple sensors with differing spatial resolution and temporal coverage (e.g., Werdell et al, 2009;Le et al, 2013;Aurin et al, 2013;Mouw et al 2013). Continuity of ocean color observations is another concern for the continued future applications of satellite algorithms (NRC, 2011), and such continuity is critical for the ability to detect trends in NPP in relation to other factors such as climate and anthropogenic impacts (e.g., Beaulieu et al, 2012).…”
Section: Biological Transformationsmentioning
confidence: 99%